High-humidity environment performance maintaining method of hafnium zirconium oxide film ferroelectric capacitor
By rapidly thermal annealing treatment and covering the oxide protective layer of hafnium zirconium oxide thin film ferroelectric capacitor devices, the problem of film and moisture reaction in the wet process is solved, and the stability and reliability of maintaining device performance in a high humidity environment is achieved.
Patent Information
- Application Number
- CN202411861698.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Hafnium zirconium oxide film is prone to react with moisture in wet process, resulting in changes in chemical composition and structural deterioration, affecting its electrical properties and long-term stability, and the device absorbs moisture in a high-humidity environment, resulting in a degradation in performance.
The ferroelectric capacitor device of hafnium zirconium oxide film treated with high humidity environment is treated with rapid thermal annealing. The annealing temperature is based on the change of Gibbs free energy of the reaction of zirconium oxide and water vapor, and is lower than the crystallization temperature of the film, and the zirconium hydroxide is redecomposed into zirconium oxide, and a layer of oxide film that does not react with water vapor is used as a protective layer.
Effectively prevent moisture invasion, reduce chemical reactions and performance degradation caused by hygroscopy, maintain the stability of the composition and structure of the film, and ensure its electrical characteristics and long-term reliability.
Smart Images

Figure CN119743958A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductors and integrated circuits, and in particular relates to a method for maintaining the high-humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor. Background Art
[0002] Hafnium zirconium oxide (HZO) films have been widely used in the field of ferroelectric memory, including ferroelectric random access memory, ferroelectric transistors and ferroelectric tunnel junctions, due to their good compatibility with standard CMOS processes and excellent miniaturization characteristics. With the continuous advancement of semiconductor technology, the demand for high-performance memory has become more urgent, and hafnium zirconium oxide films have become the focus of research due to their excellent electrical properties and stability.
[0003] At present, the research on hafnium zirconium oxide thin films mainly focuses on their failure mechanism and durability characteristics. Studies have shown that hafnium zirconium oxide thin films can achieve up to 10 14 The durability of hafnium zirconium oxide films has been shown to be very good, which provides strong support for its reliability in practical applications. However, despite the significant progress in the research on the durability of hafnium zirconium oxide films, there are still some problems that need to be solved, especially the impact of wet processing on the reliability of hafnium zirconium oxide films and the specific solution to the performance changes caused by moisture absorption of devices after preparation.
[0004] In the wet process, the hafnium zirconium oxide film easily reacts with water to form zirconium hydroxide, which may cause changes in the chemical composition and structural degradation of the film, thereby affecting its electrical properties and long-term stability. Although some theoretical analyses have explored the impact of wet processes on films, there is still a lack of specific solutions to this problem, especially how to effectively prevent moisture from having a negative impact on the film in the actual manufacturing process.
[0005] In addition, after the device is prepared, it may absorb moisture if exposed to a humid environment for a long time, further causing performance degradation. This phenomenon may cause serious problems in many applications, especially in high temperature and high humidity working environments. In order to maintain the performance of hafnium zirconium oxide thin film devices, researchers need to develop effective protection measures, such as selecting suitable protective layer materials to prevent moisture intrusion, or optimizing process parameters to reduce the hygroscopicity of the film.
[0006] In summary, although hafnium zirconium oxide thin films have made important progress in performance and durability, the impact of wet processing and ambient humidity on their performance remains a key issue that needs to be addressed. Future research should focus on exploring more effective process improvements and protective measures to ensure the performance of hafnium zirconium oxide thin films in practical applications. Summary of the invention
[0007] The purpose of the present invention is to provide a method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor in view of the influence of humidity on the film during the process of preparation and actual use of the existing hafnium zirconium oxide thin film device.
[0008] The present invention is implemented by the following technical scheme: a hafnium zirconium oxide thin film ferroelectric capacitor device treated in a high humidity environment is subjected to a rapid thermal annealing treatment. The annealing temperature is calculated by HSC simulation, which is based on the change in Gibbs free energy of the reaction between zirconium oxide and water vapor at different temperatures and is set to be lower than the crystallization temperature of the hafnium zirconium oxide film. This method can decompose the zirconium hydroxide generated in the wet process into zirconium oxide again, and the reaction formula is as follows:
[0009]
[0010] For the prepared ferroelectric capacitor device, a layer of oxide film that does not react with water vapor is covered as a protective layer to effectively isolate the hafnium zirconium oxide film from contact with water vapor. This measure can prevent moisture intrusion, reduce chemical reactions and performance degradation caused by moisture absorption, and thus ensure the stability of the film's composition and structure.
[0011] The selected oxide film has good chemical inertness and can block the influence of moisture under various environmental conditions. By introducing this protective layer, it is ensured that the hafnium zirconium oxide film is not disturbed by external water vapor during use, maintaining its electrical properties and long-term reliability.
[0012] Furthermore, by using vacuum rapid thermal annealing, the vacuum environment can effectively protect the film and the metal parts of the device.
[0013] Furthermore, the oxide protection layer is silicon oxide.
[0014] Furthermore, the hafnium zirconium oxide thin film ferroelectric capacitor adopts a metal-insulator-metal sandwich capacitor structure, which is stacked by a silicon substrate, a bottom electrode, an oxide layer, and a top electrode; the silicon substrate adopts heavily doped P-type silicon; the bottom electrode adopts TiN deposited by ALD; the oxide layer adopts a hafnium zirconium oxide thin film layer with a thickness of 10nm deposited by ALD, and the element ratio of hafnium to zirconium is 1:1; a layer of tungsten is sputtered on the hafnium zirconium oxide thin film layer as a top electrode.
[0015] Furthermore, in the preparation process of the hafnium zirconium oxide thin film ferroelectric capacitor, after the bottom electrode deposition, the hafnium zirconium oxide thin film deposition, and the top electrode deposition, the following steps are performed:
[0016] Annealing process: Place the TiN / HZO / W sample in a rapid thermal annealing chamber and evacuate the chamber until the pressure is less than 5×10 -2After Pa, nitrogen was introduced into the chamber at a rate of 1 L / min for 1 min, the nitrogen flow rate was kept constant, and the temperature was quickly raised to 500 °C. After stabilization for 1 min, nitrogen was introduced at a rate of 30 L / min to quickly cool the sample to 100 °C before taking it out;
[0017] Removal of top electrode: Soak the sample in hydrogen peroxide for 3 to 5 minutes to remove the top metal tungsten in the annealed and crystallized Si / TiN / HZO / W structure and expose the HZO film.
[0018] Treating HZO films in different humidity environments: randomly select one piece from several Si / TiN / HZO structures of the same batch without the top electrode and place it in a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 90%; select another piece and place it in a constant temperature drying oven at a temperature of 80°C and a relative humidity of 30%; perform moisture absorption treatment on the samples for 24h, 36h, and 48h respectively;
[0019] Rapid thermal annealing after moisture absorption treatment: Place the sample after moisture absorption treatment in the rapid thermal annealing chamber and evacuate the chamber until the pressure is less than 3×10 -2 After Pa, nitrogen was introduced into the chamber at a rate of 1 L / min for 2 min, and the nitrogen flow rate was kept constant. Rapid thermal annealing was performed at temperatures of 100 / 200 / 300 / 400 °C for 1 min, and then nitrogen was introduced at a rate of 30 L / min to quickly cool the sample to 80 °C before taking it out;
[0020] The top electrode is redeposited and patterned.
[0021] Furthermore, the bottom electrode deposition is specifically as follows:
[0022] Before the bottom electrode is deposited, the silicon substrate is cleaned to improve the quality of subsequent thin film deposition;
[0023] After cleaning, the substrate was dried with a nitrogen gun and then prepared for TiN deposition. ALD was used to deposit 10 nm thick TiN, with titanium tetrachloride and ammonia as precursor sources of Ti and N, respectively, and nitrogen as carrier gas and purge gas. The deposition temperature was 400 °C, the base pressure of the ALD deposition chamber of TiN was 100 Pa, and the deposition rate of TiN was 0.02 nm / cycle.
[0024] Furthermore, the hafnium zirconium oxide thin film deposition is specifically as follows:
[0025] Tetrakis(ethylmethylamino)hafnium and tetrakis(ethylmethylamino)zirconium are used as precursor materials of HfO2 and ZrO2 respectively, plasma oxygen is used as reaction gas, the overall deposition process is plasma enhanced atomic layer deposition, the growth temperature is 270°C, the base pressure of the ALD deposition chamber of the HZO film is 30Pa, and the deposition rate of HfO2 and ZrO2 is 0.1nm / cycle; by adjusting the cycle order and the number of cycles during the deposition of the HZO film, a layer of HfO2 and a layer of ZrO2 are alternately deposited, and the total number of depositions is 100cycles.
[0026] Furthermore, the top electrode deposition is specifically as follows:
[0027] The top electrode tungsten is sputtered. The sample with the hafnium zirconium oxide thin film deposited is placed in the physical vapor deposition chamber. When the chamber pressure is less than 5×10 -4 After 0.5 Pa, argon gas was introduced to adjust the chamber pressure to about 0.5 Pa, and the sputtering power was adjusted to deposit tungsten on the sample at a rate of 2 nm / min; the thickness of the tungsten electrode was 100 nm to ensure that sufficient stress was provided to the HZO film during the annealing crystallization process.
[0028] Furthermore, the top electrode patterning is specifically as follows:
[0029] Top electrode lithography: Spin-coat the photoresist at a rate of 4000 rpm / s, and heat at 105°C for 1 min to evaporate the solvent in the photoresist; use a contact exposure lithography machine to place the sample close to a mask plate with a circular array of device patterns, use near-ultraviolet light to expose the area not blocked by the mask plate, use a developer to dissolve the exposed part, rinse with deionized water, and blow dry with a nitrogen gun;
[0030] Etching: A reactive ion etching process with good collimation was used, and a mixed gas of SF6 and O2 was used as the reaction gas. The RF power of the etching was set to 100W, the inductively coupled plasma power was set to 400W, and the etching time was set to 25s to ensure that the tungsten electrode was completely etched;
[0031] De-etching and depositing the back electrode: After etching, immerse the sample in acetone and perform ultrasonic treatment until the photoresist is completely dissolved, rinse with deionized water, and blow dry with a nitrogen gun; use thermal evaporation to deposit a layer of aluminum back electrode on the back of the silicon substrate to form a good ohmic contact.
[0032] Furthermore, after the ferroelectric capacitor is prepared, plasma-enhanced chemical vapor deposition is used to grow 300nm of silicon oxide to completely cover the device area; through the surface flattening process of chemical mechanical polishing, the silicon oxide layer on the surface of the sample after the deposition of silicon oxide is ground and polished until the top electrode of the ferroelectric capacitor is exposed; at this time, the device is protected by silicon oxide and the top tungsten electrode, which can effectively isolate the influence of water vapor.
[0033] The beneficial effects of the present invention are: first, the present invention can effectively maintain the performance of the hafnium zirconium oxide film after the wet process. Second, the process steps and device structure adopted by the present invention are simple and will not increase additional costs. Third, the present invention has good compatibility with standard CMOS processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 It is a schematic structural diagram of the hafnium zirconium oxide thin film ferroelectric capacitor device in the present invention;
[0036] Figure 2 The figure is a process flow chart for preparing the hafnium zirconium oxide thin film ferroelectric capacitor device of the present invention;
[0037] Figure 3 The process simulation flow of the high humidity environment treatment of the hafnium zirconium oxide film in the present invention;
[0038] Figure 4 is the Gibbs free energy of the reaction between zirconium oxide and water vapor at different temperatures in the present invention;
[0039] Figure 5 is the polarization intensity of the sample treated in a high humidity environment after annealing at different temperatures;
[0040] Figure 6 is the Gibbs free energy of reaction of different oxide films with water vapor at room temperature and pressure in the present invention;
[0041] Figure 7 The figure is a schematic diagram of the structure and process flow of the external oxide protective film in the present invention. DETAILED DESCRIPTION
[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0043] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0044] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0045] Figure 1 The schematic diagram of the hafnium zirconium oxide thin film ferroelectric capacitor structure of the present invention is shown. A metal-insulator-metal (MIM) sandwich capacitor structure is used, and the capacitor structure is stacked by a silicon substrate, a bottom electrode, an oxide layer, and a top electrode. In the capacitor structure, heavily doped P-type silicon with a (100) crystal orientation is selected as the substrate material, mainly considering the low resistivity (<0.001Ω·cm) of heavily doped P-type silicon and the ease of forming ohmic contact with metals such as aluminum, which is convenient for subsequent wiring tests. The bottom electrode is titanium nitride (TiN) deposited by atomic layer deposition (ALD). TiN can not only provide stress for the HZO film during annealing, but also serve as a barrier layer to prevent external impurities from diffusing into the HZO film. The oxide layer is a 10nm thick hafnium zirconium oxide thin film layer deposited by ALD, with the element ratio of hafnium to zirconium being 1:1; on the HZO film, a layer of tungsten electrode is sputtered and deposited as the top electrode of the device to provide stress in the subsequent annealing and crystallization process to improve the ferroelectricity of the HZO film.
[0046] Figure 2 The preparation process of hafnium zirconium oxide thin film ferroelectric capacitor is mainly divided into four parts:
[0047] (1) Bottom electrode deposition
[0048] Before the bottom electrode is deposited, the silicon substrate is cleaned to remove residual organic matter, metal ions, etc. on the surface to improve the quality of subsequent thin film deposition. The cleaning steps are as follows:
[0049] a) Acetone solution cleaning: Soak the substrate in an acetone solution at room temperature, ultrasonicate for 5 minutes, and then rinse with deionized water. Acetone can effectively remove organic matter on the surface of the substrate.
[0050] b) Cleaning with diluted hydrofluoric acid (HF) solution: The substrate was immersed in a 2% by volume HF solution for 1 min and then rinsed with deionized water. This step is to remove the natural oxide layer on the surface of the silicon substrate.
[0051] c) SC-1 solution cleaning: The substrate that has undergone the above cleaning process is immersed in SC-1 solution (NH4OH:H2O2:H2O=1:1:5) at a temperature of 80°C for 5 minutes, and then rinsed with deionized water. The SC-1 solution can effectively remove solid particles and organic matter on the surface of the substrate.
[0052] d) SC-2 solution cleaning: The substrate that has undergone the above cleaning process is immersed in a SC-2 solution (HCl:H2O2:H2O=1:1:6) at a temperature of 80°C for 10 minutes, and then rinsed with deionized water. This step is to remove ions and heavy metal particles on the surface of the silicon substrate.
[0053] After cleaning, the substrate was dried with a nitrogen gun and then prepared for TiN deposition. ALD was used to deposit 10nm thick TiN, with titanium tetrachloride (TiCl4) and ammonia as precursor sources for Ti and N, respectively, and nitrogen as carrier gas and purge gas. The deposition temperature was about 400°C, the base pressure of the ALD deposition chamber for TiN was 100Pa, and the deposition rate of TiN was about 0.02nm / cycle.
[0054] (2) Hafnium Zirconium Oxide Thin Film Deposition
[0055] After the bottom electrode TiN is deposited, the HZO film is deposited. Tetra(ethylmethylamino)hafnium and tetra(ethylmethylamino)zirconium are used as precursor materials for hafnium oxide (HfO2) and zirconium oxide (ZrO2), respectively. Plasma oxygen is used as the reaction gas. The overall deposition process is plasma enhanced atomic layer deposition. The growth temperature is 270°C. The base pressure of the ALD deposition chamber of the HZO film is 30Pa. The deposition rate of HfO2 and ZrO2 is about 0.1nm / cycle. By adjusting the cycle order and the number of cycles during the deposition of the HZO film, a layer of HfO2 and a layer of ZrO2 are alternately deposited, and the total number of depositions is 100 cycles.
[0056] (3) Top electrode deposition
[0057] The top electrode tungsten (W) was sputtered. The sample deposited in step (2) was placed in a physical vapor deposition chamber. When the chamber pressure was less than 5×10 -4 After 0.5 Pa, argon gas was introduced to adjust the chamber pressure to about 0.5 Pa, and the sputtering power was adjusted to deposit tungsten on the sample at a rate of 2 nm / min. The thickness of the tungsten electrode was about 100 nm to ensure that sufficient stress was provided to the HZO film during the annealing crystallization process.
[0058] (4) Annealing crystallization and top electrode patterning
[0059] a) Annealing process
[0060] The TiN / HZO / W sample was placed in a rapid thermal annealing chamber and evacuated to a chamber pressure of less than 5×10 -2 Pa, nitrogen (N2) was introduced into the cavity at a rate of 1 L / min for 1 min, the N2 flow rate was kept constant, the temperature was quickly raised to 500 °C, and after stabilizing for 1 min, nitrogen was introduced at a rate of 30 L / min to quickly cool the sample to 100 °C before taking it out.
[0061] b) Top electrode lithography
[0062] Spin-coat the photoresist AR-P 5350 at a rate of 4000rpm / s. After the spin coating is completed, heat it at 105℃ for 1min to evaporate the solvent in the photoresist and improve the adhesion of the photoresist on the top electrode tungsten. Then use a contact exposure lithography machine to place the sample close to the mask plate with a circular array arrangement of device patterns, use near-ultraviolet light to expose the area not blocked by the mask plate, use the configured developer (AR 300-26:H2O=1:7) to dissolve the exposed part, rinse with deionized water and blow dry with a nitrogen gun.
[0063] c) Etching
[0064] In order to ensure the accuracy of the device pattern, a reactive ion etching process with better collimation is adopted. A mixed gas of SF6 and O2 is used as the reaction gas. The RF power of the etching is set to 100W, the inductively coupled plasma power is 400W, and the etching time is set to 25s to ensure that the tungsten electrode is completely etched.
[0065] d) Deposition of back electrode
[0066] After etching, the sample was immersed in acetone and ultrasonically treated until the photoresist was completely dissolved, rinsed with deionized water, and dried with a nitrogen gun. A layer of aluminum back electrode was deposited on the back of the silicon substrate by thermal evaporation to form a good ohmic contact.
[0067] Figure 3 The process flow simulation of the high humidity environment treatment of the HZO film in the present invention and the subsequent rapid thermal annealing recovery process flow are as follows:
[0068] (1) Top electrode removal
[0069] The sample was soaked in hydrogen peroxide for 3 to 5 minutes to remove the top metal tungsten in the annealed and crystallized Si / TiN / HZO / W structure and expose the HZO film for subsequent high humidity environment treatment.
[0070] (2) Treatment of HZO films in different humidity environments
[0071] A piece of Si / TiN / HZO structure with the top electrode removed was randomly selected from the same batch and placed in a constant temperature and humidity chamber at 80°C and 90% relative humidity; another piece was selected and placed in a constant temperature drying chamber at 80°C and 30% relative humidity. The samples were subjected to moisture absorption treatment for 24h, 36h, and 48h respectively.
[0072] (3) Rapid thermal annealing after sample moisture absorption treatment
[0073] The sample after moisture absorption treatment was placed in a rapid thermal annealing chamber and evacuated to a chamber pressure of less than 3×10 -2 Pa, nitrogen (N2) was introduced into the cavity at a rate of 1 L / min for 2 min, and the N2 flow rate was kept unchanged. Rapid thermal annealing was performed at temperatures of 100 / 200 / 300 / 400°C for 1 min, and then nitrogen was introduced at a rate of 30 L / min to quickly cool the sample to 80°C before taking it out.
[0074] (4) Re-deposition of top electrode and patterning
[0075] The specific process flow is the same as the preparation process of the conventional ferroelectric capacitor mentioned above.
[0076] Figure 4 is the Gibbs free energy of the reaction between zirconium oxide and water vapor at different temperatures. The Gibbs free energy calculation formula is:
[0077] ΔG=ΔH-TΔS
[0078] Among them, ΔH is the reaction enthalpy change, ΔS is the reaction entropy change, and T is the reaction temperature. When ΔG<0, the energy of the system decreases after the reaction, indicating that the reaction can proceed spontaneously. The larger the absolute value of ΔG, the faster the reaction rate. On the contrary, when ΔG>0, the reaction is non-spontaneous and tends to proceed in the reverse direction. The HSC software is used to calculate the Gibbs free energy of the reaction of zirconium oxide with water vapor at different temperatures. The Gibbs free energy of the reaction of zirconium oxide with water vapor is greater than zero when it exceeds 260°C. At this time, the reaction tends to proceed in the reverse direction, and zirconium hydroxide is more likely to decompose into zirconium oxide and water. In actual annealing treatment, a temperature exceeding 260°C is more beneficial to the recovery of device performance.
[0079] Figure 5 The polarization intensity of the sample after annealing at different temperatures after being treated in a high humidity environment of 80°C and 90% for 48 hours, where 2P r is the sample polarization intensity. Figure 4The calculation results show that when the annealing temperature is lower than 260℃, the recovery of polarization intensity is small, which is quite different from that of the sample without moisture absorption treatment. As the annealing temperature rises to 300℃, the polarization intensity recovers to the same level as that of the HZO film without moisture absorption treatment. At 400℃, due to the annealing recovery effect, the polarization intensity is partially improved compared with the performance of the HZO film without moisture absorption treatment.
[0080] Figure 6 The Gibbs free energy of reaction of different oxide films in the present invention with water vapor at room temperature and pressure. The data in the figure show that the Gibbs free energy of reaction of most High-k oxide films with water vapor is less than zero. They are easy to react with water vapor in a high humidity environment to generate corresponding hydroxides, which has an adverse effect on the performance of HZO films. Based on the calculated data, cerium oxide, silicon oxide, scandium trioxide and hafnium oxide are not easy to react with water vapor and can maintain good properties in a high humidity environment. Considering the compatibility of the deposition process and the device, as well as the cost and time of thin film deposition, silicon oxide is selected as the thin film isolation layer to protect the device.
[0081] Figure 7 The schematic diagram and process flow of the structure of the external oxide protective film in the present invention are as follows. After the ferroelectric capacitor device is prepared, a 300nm silicon oxide is grown by plasma enhanced chemical vapor deposition to completely cover the device area. Through the surface flattening process of chemical mechanical polishing (CMP), the silicon oxide layer on the surface of the sample after the silicon oxide is deposited is ground and polished until the top electrode of the ferroelectric capacitor is exposed. At this time, the device is protected by silicon oxide and the top tungsten electrode, which can effectively isolate the influence of water vapor.
[0082] The above description is merely a preferred embodiment of one or more embodiments of the present specification and is not intended to limit one or more embodiments of the present specification. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present specification shall be included in the scope of protection of one or more embodiments of the present specification.
Claims
1. A method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor, characterized in that: The method includes: Determining a rapid thermal annealing temperature according to the change in Gibbs free energy of the reaction between zirconium oxide and water vapor at different temperatures; the rapid thermal annealing temperature is lower than the crystallization temperature of the hafnium zirconium oxide film and higher than the temperature at which the Gibbs free energy of the reaction between zirconium oxide and water vapor is zero, so as to achieve the decomposition of zirconium hydroxide; An oxide protective layer is selected based on the Gibbs free energy of reaction between different oxide materials and water vapor at room temperature and pressure; the Gibbs free energy of reaction between the oxide protective layer and water vapor at room temperature and pressure is greater than zero, and the corresponding hydroxide cannot be generated, thereby effectively isolating the hafnium zirconium oxide film from contact with water vapor and protecting the internal components of the hafnium zirconium oxide film from the influence of external humidity.
2. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 1, characterized in that: Using vacuum rapid thermal annealing, the vacuum environment can effectively protect the film and the metal parts of the device.
3. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 1, characterized in that: The oxide protection layer is silicon oxide.
4. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 1, characterized in that: The hafnium zirconium oxide thin film ferroelectric capacitor adopts a metal-insulator-metal sandwich capacitor structure, which is composed of a silicon substrate, a bottom electrode, an oxide layer, and a top electrode stacked together; the silicon substrate adopts heavily doped P-type silicon; the bottom electrode adopts TiN deposited by ALD; the oxide layer adopts a hafnium zirconium oxide thin film layer with a thickness of 10nm deposited by ALD, and the element ratio of hafnium to zirconium is 1:1; a layer of tungsten is sputtered and deposited on the hafnium zirconium oxide thin film layer as a top electrode.
5. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 1, characterized in that: In the preparation process of the hafnium zirconium oxide thin film ferroelectric capacitor, after the bottom electrode is deposited, the hafnium zirconium oxide thin film is deposited, and the top electrode is deposited, performing: Annealing process: Place the TiN / HZO / W sample in a rapid thermal annealing chamber and evacuate the chamber until the pressure is less than 5×10 -2 After Pa, nitrogen was introduced into the chamber at a rate of 1 L / min for 1 min, the nitrogen flow rate was kept constant, and the temperature was quickly raised to 500 °C. After stabilization for 1 min, nitrogen was introduced at a rate of 30 L / min to quickly cool the sample to 100 °C before taking it out; Removal of top electrode: Soak the sample in hydrogen peroxide for 3 to 5 minutes to remove the top metal tungsten in the annealed and crystallized Si / TiN / HZO / W structure and expose the HZO film. Treating HZO films in different humidity environments: randomly select one piece from several Si / TiN / HZO structures of the same batch without the top electrode and place it in a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 90%; select another piece and place it in a constant temperature drying oven at a temperature of 80°C and a relative humidity of 30%; perform moisture absorption treatment on the samples for 24h, 36h, and 48h respectively; Rapid thermal annealing after moisture absorption treatment: Place the sample after moisture absorption treatment in the rapid thermal annealing chamber and evacuate the chamber until the pressure is less than 3×10 -2 After Pa, nitrogen was introduced into the chamber at a rate of 1 L / min for 2 min, and the nitrogen flow rate was kept constant. Rapid thermal annealing was performed at temperatures of 100 / 200 / 300 / 400 °C for 1 min, and then nitrogen was introduced at a rate of 30 L / min to quickly cool the sample to 80 °C before taking it out; The top electrode is redeposited and patterned.
6. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 5, characterized in that: The bottom electrode deposition is specifically as follows: Before the bottom electrode is deposited, the silicon substrate is cleaned to improve the quality of subsequent thin film deposition; After cleaning, the substrate was dried with a nitrogen gun and then prepared for TiN deposition. ALD was used to deposit 10 nm thick TiN, with titanium tetrachloride and ammonia as precursor sources of Ti and N, respectively, and nitrogen as carrier gas and purge gas. The deposition temperature was 400 °C, the base pressure of the ALD deposition chamber of TiN was 100 Pa, and the deposition rate of TiN was 0.02 nm / cycle.
7. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 5, characterized in that: The hafnium zirconium oxide thin film deposition is specifically as follows: Tetrakis(ethylmethylamino)hafnium and tetrakis(ethylmethylamino)zirconium are used as precursor materials of HfO2 and ZrO2 respectively, plasma oxygen is used as reaction gas, the overall deposition process is plasma enhanced atomic layer deposition, the growth temperature is 270°C, the base pressure of the ALD deposition chamber of the HZO film is 30Pa, and the deposition rate of HfO2 and ZrO2 is 0.1nm / cycle; by adjusting the cycle order and the number of cycles during the deposition of the HZO film, a layer of HfO2 and a layer of ZrO2 are alternately deposited, and the total number of depositions is 100cycles.
8. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 5, characterized in that: The top electrode deposition is specifically as follows: The top electrode tungsten is sputtered. The sample with the hafnium zirconium oxide thin film deposited is placed in the physical vapor deposition chamber. When the chamber pressure is less than 5×10 -4 After 0.5 Pa, argon gas was introduced to adjust the chamber pressure to about 0.5 Pa, and the sputtering power was adjusted to deposit tungsten on the sample at a rate of 2 nm / min; the thickness of the tungsten electrode was 100 nm to ensure that sufficient stress was provided to the HZO film during the annealing crystallization process.
9. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 5, characterized in that: The top electrode patterning is specifically as follows: Top electrode lithography: Spin-coat the photoresist at a rate of 4000 rpm / s, and heat at 105°C for 1 min to evaporate the solvent in the photoresist; use a contact exposure lithography machine to place the sample close to a mask plate with a circular array of device patterns, use near-ultraviolet light to expose the area not blocked by the mask plate, use a developer to dissolve the exposed part, rinse with deionized water, and blow dry with a nitrogen gun; Etching: A reactive ion etching process with good collimation was used, and a mixed gas of SF6 and O2 was used as the reaction gas. The RF power of the etching was set to 100W, the inductively coupled plasma power was set to 400W, and the etching time was set to 25s to ensure that the tungsten electrode was completely etched; De-etching and depositing the back electrode: After etching, immerse the sample in acetone and perform ultrasonic treatment until the photoresist is completely dissolved, rinse with deionized water, and blow dry with a nitrogen gun; use thermal evaporation to deposit a layer of aluminum back electrode on the back of the silicon substrate to form a good ohmic contact.
10. The method for maintaining the high humidity environment performance of a hafnium zirconium oxide thin film ferroelectric capacitor according to claim 1, characterized in that: After the ferroelectric capacitor is prepared, plasma-enhanced chemical vapor deposition is used to grow 300nm of silicon oxide to completely cover the device area. Through the surface flattening process of chemical mechanical polishing, the silicon oxide layer on the surface of the sample after the deposition of silicon oxide is ground and polished until the top electrode of the ferroelectric capacitor is exposed. At this time, the device is protected by silicon oxide and the top tungsten electrode, which can effectively isolate the influence of water vapor.
Citation Information
Patent Citations
Hafnium oxide-based ferroelectric film capacitor and preparation method thereof
CN117580445A
Methods to Improve Electrical Performance of ZrO2 Based High-K Dielectric Materials for DRAM Applications
US20150228710A1
Electronic device including hermetic micro-cavity and methods of preparing the same
US20210183647A1
Capacitor for dynamic random access memory, dram including the same and methods of fabricating thereof
US20220246716A1